A Retrospective Analysis of Secondary Revisions after Face Transplantation: Assessment of Outcomes, Safety, and Feasibility. Issue 4 (October 2016) - Aycart, Mario A.; Alhefzi, Muayyad; Kueckelhaus, Maximilian; Krezdorn, Nicco; Bueno, Ericka M.; Caterson, Edward J.; Pribaz, Julian J.; Pomahac, Bohdan
Abstract : Background: Face transplantation has emerged as a viable option for certain patients in the treatment of devastating facial injuries. However, as with autologous free tissue transfer, the need for secondary revisions in face transplantation also exists. The authors' group has quantified the number of revision operations in their cohort and has assessed the rationale, safety, and outcomes of posttransplantation revisions. Methods: A retrospective analysis of prospectively collected data of the authors' seven face transplants was performed from April of 2009 to July of 2015. The patients' medical records, preoperative facial defects, and all operative reports (index and secondary revisions) were critically reviewed. Results: The average number of revision procedures was 2.6 per patient (range, zero to five procedures). The median time interval from face transplantation to revision surgery was 5 months (range, 1 to 10 months). Most interventions consisted of debulking of the allograft, superficial musculoaponeurotic system plication and suspension, and local tissue rearrangement. There were no major infections, allograft skin flap loss, or necrosis. One patient suffered a postoperative complication after autologous fat grafting in the form of acute rejection that resolved with pulse steroids. Conclusions: Secondary revisions after face transplantation are necessary components of care, as they are after most conventional free tissue transfers. Secondary revisions after face transplantation at the authors' institution have addressed both aesthetic and functional reconstructive needs, and these procedures have proven to be safe in the context of maintenance immunosuppression. Patient and procedure selection along with timing are essential to ensure patient safety, optimal function, and aesthetic outcomes. CLINICAL QUESTION/LEVEL OF EVIDENCE: Therapeutic, V.